For the edition of Vincenzo Monti's 'Il Fanatismo', 'La supersizione', and 'Il pericolo' (Prassi Ecdotiche della Modernità Letteraria, 2021)
Il Fanatismo, La Superstizione and Il Pericolo, poems composed in tercets dating back to 1797, represent the first poetic evidence of Vincenzo Monti’s pro-revolution position. The analysis of the different editions of these textes results in the conclusion that a work of re-writing work has been carried out throughout the entire Jacobean period.